Pole pracy Misjonarzy Oblatów Maryi Niepokalanej w Afryce w XIX wieku - Kluj, Wojciech (Annales Missiologici Posnanienses, 2012)
In 1850 the Holy See entrusted missionary work in South Africa to a young at that time congregation of the Missionary Oblates of Mary Immaculate. Oblates undertook that work and after some time divided their work in the 19th century into five different regions. At first they began their work in Natal, after that in Basutoland (now Lesotho), in the Free Orange State, in Transvaal, and at the end of the century also in Cymbebasie (today Namibia). As the first Oblate mission in Africa, this activity remains a point of reference to the further development of the conception of the Oblate missions in Africa.